Pediococcus pentosaceus SB83 as a potential probiotic incorporated in a liquid system for vaginal delivery - Borges, S. (2015)
Pediococcus pentosaceus SB83 is a bacteriocinogenic culture having potential use as a vaginal probiotic. The objective of this study was to evaluate the behaviour of P. pentosaceus SB83 incorporated in a liquid system for eventually formulating a gel for vaginal delivery. The vaginal probiotic incorporated into glycerol was able to survive in simulated vaginal fluid at normal vaginal pH (4.2) and at pH of vaginal infections (5.5 and 6.5). The probiotic can be stored at 4 °C for a longer period of time than at room temperature, however, after 13 weeks of storage at low temperature, there was a total loss of viable cells. The probiotic strain incorporated into glycerol showed bacteriocinogenic activity in simulated vaginal fluid, although the antimicrobial activity against Listeria monocytogenes declined during storage. This study showed the behaviour of P. pentosaceus SB83 in glycerol and in simulated vaginal fluid. However, it is necessary to optimise the formulation to produce an actively probiotic vaginal gel.